2014
DOI: 10.3390/vetsci1010005
|View full text |Cite
|
Sign up to set email alerts
|

Filarial Nematode Infection in Ixodes scapularis Ticks Collected from Southern Connecticut

Abstract: It was recently demonstrated that the lone star tick Amblyomma americanum could harbor filarial nematodes within the genus Acanthocheilonema. In this study, Ixodes scapularis (deer) ticks collected from Southern Connecticut were evaluated for their potential to harbor filarial nematodes. Non-engorged nymphal and adult stage Ixodes scapularis ticks were collected in Southern Connecticut using the standard drag method. In situ hybridization with filarial nematode specific sequences demonstrated the presence of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
4
23
0
1
Order By: Relevance
“…The low overall infection prevalence in this study is similar to that found in A. americanum ticks in Maryland, but is markedly smaller than that detected in I. scapularis populations in Connecticut (Namrata et al, 2014; Zhang et al, 2011). This phenomenon could reflect that I. scapularis is more favorable to infection and development of nematodes in this clade than A. americanum .…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The low overall infection prevalence in this study is similar to that found in A. americanum ticks in Maryland, but is markedly smaller than that detected in I. scapularis populations in Connecticut (Namrata et al, 2014; Zhang et al, 2011). This phenomenon could reflect that I. scapularis is more favorable to infection and development of nematodes in this clade than A. americanum .…”
Section: Discussionsupporting
confidence: 60%
“…This tick-borne nematode clade was previously reported to be of the genus Acanthocheilonema (Zhang et al, 2011; Namrata et al, 2014), but further analysis using newly available nematode 12S sequences in the Gen-Bank database suggests that these nematodes likely belong to the genus Monanema (Fig. 1).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…After this initial report, the identity of this agent remained obscure for the next three decades. In 2014, 12S rRNA gene sequences homologous to sequences from larial nematodes were detected in I. scapularis ticks in Connecticut [3]. Subsequent metagenomic analyses of I. scapularis from Wisconsin and our study from New York and Connecticut also reported Filarioidea sequences [4,5].…”
Section: Introductionmentioning
confidence: 52%